(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2025)
This study examines the content moderation policies developed and implemented by Youtube between the election period of 2022 and January 8, 2023. It builds on concepts from platform studies on the governance challenges and problems faced by these technological corporations. The study employs digital dynamic archiving methods to examine the removal status of 193,429 videos. The findings show that deletion rates are higher than in other cases studied in the specialized literature. YouTube does not provide a clear justification for which policies were violated and why. We discuss the implications for memory and studies on contexts of risk to democracy, given that some channels have deleted more than 90% of their production. The remainder of this study evaluates the consequences for platform governance research and future research directions.